Comparative characterization of key compounds of Sauce-flavored rounded-Baijiu in northern and southern China and the potential possibility of similar quality of their combined products - Hexia Ding; Jiekai Yang; Mai Cheng; Xuanchen Li; Maodie Zeng; Wei Yang; Qian Wu; Xiaoye Luo; Juan Zhao; Xiande Li; Shuyi Qiu; Jianli Zhou (Food Chemistry: X, 2024)
The flavor characteristics and sensory attributes of northern Sauce-flavored rounded-Baijiu (NR) and southern Sauce-flavored rounded-Baijiu (SR) were systematically studied. A total of 56 major flavor compounds were quantitatively detected through Gas chromatography-flame ionization detection (GC-FID). Besides, 20 kinds of key aroma compounds and 7 significant differential compounds were identified by calculating the odor activity values (OAVs) and orthogonal partial least squares discriminant analysis (OPLS-DA) of flavor compounds in NR and SR. And then, the relationship between sensory attributes and key aroma compounds were investigated by network analysis. Furthermore, A group of combined-Baijiu (the ratios of the first to the fifth round of Sauce-flavored Baijiu in the north (NR1–5) were 5 % NR1, 35 % NR2, 30 % NR3, 20 % NR4, 10 % NR5) was closer to the style known for blending different proportions of SR into the combined-Baijiu. This study provided a guiding significance for the standardized production of sauce-flavored Baijiu.